Exploration of RNAi-based theraupeutic strategies for Dominant Dystrophic Epidermolysis Bullosa - Morgan, Clare (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2011)
The main focus of this Ph.D. thesis centres on exploration of a potential gene therapy for treatment of the dystrophic form of the rare blistering skin disorder Epidermolysis Bullosa (EB). There are three main subtypes of the disease, characterised by mutations of different genes important for maintaining the integrity of epithelial lined or surfaced tissue layers of the human body, but all of which result in a phenotype of fragility of the skin and mucous membranes (Solovan et al, 2005; Fine, 2010a). All three forms of the disease are genetically heterogeneous and symptoms range in severity according to the mutation in question.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.